A case of cooperative breeding in the European Starling, Sturnus vulgaris - Hazel Nichols (Ecology and Evolution, 2022)
Cooperative breeding, where individuals other than the parents help to raise offspring, occurs in only ~9% of bird species. Although many starlings (Sturnidae) are cooperative breeders, the European starling (Sturnus vulgaris) has rarely been observed exhibiting this behavior. Only two other records exist, one of which was limited to a juvenile giving food to chicks that had already been collected by a parent (and hence providing limited help). Herein, we report a case of cooperative breeding by a juvenile European starling, which represents the second with any evidence of the juvenile collecting food independently and the first to document the extent of such help in the form of feeding rates. Over a period of at least 3 days, a juvenile starling assisted two parents to feed their second brood of the year, and it fed the chicks at the same rate as the adults (~3.5 feeds per hour). In considering potential explanations for this behavior, we conducted an ancestral state estimation of cooperative breeding across starlings and were able to eliminate the possibility that this is a rarely expressed behavior inherited from cooperatively breeding ancestors. Instead, we propose that our observations point to a behavioral innovation, which may be in response to environmental change such as climate change (which has previously been associated with cooperative breeding). Researchers working on birds should be alert to such behavior to determine whether this apparently new breeding strategy will increase as a potential adaptation to environmental change.